(untitled) (Comparative Professional Pedagogy, 2023)
The article analyzes applied linguistics as a field of knowledge in the Canadian experience and its interdisciplinary interactions. It is pointed out that interdisciplinary interaction with other sciences such as psychology, sociology, informatics, semiotics, cybernetics, etc. determined the evolution of linguistic research in recent decades. In the result of the integration of scientific efforts, such complex sciences as psycholinguistics, sociolinguistics, cognitive linguistics, computer linguistics, neurolinguistics, etc. have emerged. It is noted that the interdisciplinary interaction of applied linguistics contributes to its formation as a field of knowledge, enriching research and solving complex linguistic problems. It is established that the connection of applied linguistics with other scientific fields contributed to a comprehensive understanding of language and its use in various fields. The nature, advantages and influence of interdisciplinary connections of applied linguistics in Canada with other fields of knowledge are analyzed. In particular, the connection of applied linguistics with psychology offers an understanding of the cognitive processes involved in language acquisition. At their intersection, the subfield of psycholinguistics emerges. Leading researchers have identified psycholinguistics as the study of how people perceive, create, and understand language. It is noted that the interdisciplinary connection of applied linguistics and sociology solves the problems of language identity, diversity and the influence of social variables on language learning and use. It is determined that the connection of applied linguistics with information technologies, in particular with computational linguistics, contributes to the progress of computer-aided language learning (CALL) and innovative approaches to language learning. It is highlighted that interdisciplinary collaborations in applied linguistics have many advantages, such as a deeper and more thorough comprehension of language-related problems, creative approaches to research, and the creation of workable solutions to real-world language problems.